Effectiveness of Acupuncture on the Quality of Life in Allergic Rhinitis Patients: Meta Analysis - Widiatmaja, I Gusti Bagus Panji; Raharjo, Setyo Sri; Widyaningsih, Vitri (Masters Program in Public Health, Sebelas Maret University, 2024)
Background: Allergic rhinitis (AR) is one of the most common health problems experienced by people around the world. WHO ARIA defines allergic rhinitis as a disorder of the nose accompanied by symptoms of sneezing, runny nose, itching, and nasal congestion e after the nasal mucosa is exposed to allergens mediated by immunoglobulin E (IgE). Many studies have proven the impact of acupuncture on the immune system. This study aims to examine and estimate the effectiveness of acupuncture therapy for allergic rhinitis patients based on the results of previous similar studies. Subject and Method: This study is a systematic review and meta-analysis, with PICO as the following Population: allergic rhinitis patients. Intervention: acupuncture therapy. Comparison: sham/placebo acupuncture. Outcome: quality of life. The articles used in this study were obtained from several databases including Google Scholar, MEDLINE/PubMed, Science Direct, Hindawi, Europe PMC and Springer Link. These articles were collected for 1 month. The keywords to search for articles are as follows: